EMPLOYMENT AGREEMENT BETWEEN HOSPITALS AND THE HEALTH SOCIAL SECURITY MANAGEMENT AGENCY (BPJS) REVIEWED FROM THE LAW OF ENGAGEMENT IN INDONESIA (INTERNATIONAL SEMINAR, 2025)
The purpose of this study is to analyze the employment agreement between hospitals and the Health Social Security Administration Agency (BPJS) in Indonesia from the perspective of contract law. The method used is normative juridical with a literature study approach, which examines laws and regulations, cooperation contracts, and related legal doctrines. The analysis was carried out qualitatively through the interpretation of legal norms and comparison of the practice of implementing work agreements. The results of the study show that the work agreement between the hospital and BPJS Kesehatan is a legally binding contract based on Law Number 24 of 2011 and its implementing regulations. This agreement regulates the rights and obligations in detail for both parties, such as the payment of claims by BPJS and the hospital's obligation to provide services according to standards without additional charges. The implementation of the agreement faces the challenge of power imbalance where BPJS applies the clause unilaterally. The dispute resolution mechanism is prioritized through deliberation and mediation, and if it is not achieved, it can be forwarded to the Clinical Advisory Board or the district court. Serious violations such as fraud can proceed to the criminal realm, but civil disputes must still be resolved to uphold the rights and obligations of the parties.